Proteomics in food science : from farm to fork - Colgrave, Michelle L. (Academic Press, 2017)
Proteomics in Food Science: From Farm to Fork is a solid reference providing concepts and practical applications of proteomics for those in various disciplines of food science. The book covers a range of methods for elucidating the identity or composition of specific proteins in foods or cells related to food science, from spoilage organisms, to edible components. A variety of analytical platforms are described, ranging from the usage of simple electrophoresis, to more sophisticated mass spectrometry and bio-informatic platforms. The book is designed for food scientists, technologists, food industry workers, microbiologists, and public health workers, and can also be a valuable reference book for students.- Resumé vydavatel
Keywords: proteomika; potraviny; potravinářský průmysl; proteomics; foodstuffs; food industry; kolektivní monografie; elektronické knihy; collective monographs; electronic books